Prototipe Sistem Monitoring, Penyaringan dan Pembuangan Asap Rokok Otomatis dalam Ruangan Berbasis NodeMCU ESP-32 - Hernawati, Hernawati; Sayuti, Sayuti; Iswanto, Iswanto (Journal of Computer System and Informatics (JoSYC), 2024)
Cigarette smoke is a source of pollution which contains various substances such as nicotine, tar, carbon monoxide gas (CO) and carbon dioxide gas (CO2) which harm the body's health. Cigarette smoke is inhaled by active smokers and passive smokers, namely people who do not smoke, but are exposed to and inhale cigarette smoke from the surrounding environment. WHO data shows that 8 million deaths were caused by cigarette smoke, 1.2 million of which were passive smokers. Currently, in several places special smoking rooms have been provided, however, cigarette smoke flowing outside the room still causes pollution. Reducing air pollution is crucial and must be provided with a solution, including by filtering the air from smoking rooms. This research aims to build a prototype system for monitoring, filtering and automatically disposing of indoor cigarette smoke. The prototype reduces the level of cigarette smoke in the room until it reaches normal conditions (400-1000 ppm) and filters the cigarette smoke produced from the smoking room before it is released outside the room. The NodeMCU ESP-32 is used as a microcontroller and is equipped with an MQ-2 sensor which is capable of detecting various types of gas including carbon monoxide (CO), carbon dioxide (CO2) and cigarette smoke, as well as activated carbon as the main ingredient in the cigarette smoke filtering process. Activated carbon has high absorption capacity so it is effective as an air purification medium. The system test results succeeded in detecting, monitoring, filtering and disposing of filtered smoke with an average level of filtered cigarette smoke of 249.5 ppm.